Suffering around astronomical and biological clocks along with artificial intelligence - Iabluchanskyi, Mykola (My University, 2023)
The problem is still far from its comprehensive solution, so it seemed interesting to me to compare how it is seen, so to speak, by two artificial intelligences (AI) ChatGPT and Bard
Here I present to you these experiences of mine. Ideas are, of course, my property, not the property of the AI.
Keywords: astronomical age; biological age